ASSESSMENT OF PHARMACISTS' ATTITUDE TOWARDS THE IMPORTANCE OF REPORTING ADVERSE REACTIONS TO MEDICINES - Ткачова, О.В.; Бутко, Я.О.; Андріяненков, О.В.; Березняков, А.В. (SWorldJournal, 2025)
Adverse drug reactions (ADRs) pose a significant threat to the health of patients and are an important problem in the field of healthcare. An effective pharmacovigilance system depends on the active participation of pharmaceutical professionals, in partic